Real expectations: Replacing rational expectations with survey expectations in dynamic macro models - Jeff Fuhrer (Federal Reserve Bank of Boston, 2013)
This paper examines the implications of changing the expectations assumption that is embedded in nearly all current macroeconomic models. The paper substitutes measured or real expectations for rational expectations in an array of standard macroeconomic relationships, as well as in a DSGE model. The author finds that the use of survey measures of expectations - for near-term inflation, long-term inflation, unemployment, and short-term interest rates - improves performance along a variety of dimensions. Survey expectations exhibit strong correlations to key macroeconomic variables. Those correlations may be given a structural interpretation in a DSGE context. Including survey expectations helps to identify key slope parameters in standard relationships, and eliminates the need for having lagged dependent variables in structural models that is often motivated by indexation for prices and habit formation for consumption. Including survey expectations also obviates the need for autocorrelated structural shocks in the key equations. In a head-to-head empirical test, the weight placed on the DSGE model's rational expectations is essentially zero and the weight on survey expectations is one. The paper also discusses the modeling complications that arise once the rational expectations assumption is abandoned, and proposes methods for endogenizing survey expectations in a general equilibrium macro model.
Keywords: E32; E52; 330; rational expectations; survey expectations; DSGE models; habit formation